1991
DOI: 10.1111/j.1467-9310.1991.tb00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the integration of technical functions for efficient product development

Abstract: It is probably safe to say that today it is universally accepted and often common knowledge that cooperation between product development and the market functions is crucial for the ability of companies to develop market oriented products. Likewise, there are some strong indications that well functioning cooperation between production and product development is crucial for the development of products that are efficient to manufacture. However, no satisfactory solutions have yet been found to the issues of integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Moreover, they have to implement new product design according to the goal set as part of the new product development strategy (Cooper and Kleinschmidt 1987, Souder and Song 1997, Ulrich and Pearson 1998. Researchers also claim that integrating product development in an enterprise can promote new product development performance (Gupta et al 1985, Carlsson 1991, Pinto et al 1993, Olson 1994, Griffin and Hauser 1996, Ruekert and Walker 1997, Rusinko 1997, Sobek et al 1998). On the other hand, numerous studies have shown that 'design' can provide an important integral resource.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, they have to implement new product design according to the goal set as part of the new product development strategy (Cooper and Kleinschmidt 1987, Souder and Song 1997, Ulrich and Pearson 1998. Researchers also claim that integrating product development in an enterprise can promote new product development performance (Gupta et al 1985, Carlsson 1991, Pinto et al 1993, Olson 1994, Griffin and Hauser 1996, Ruekert and Walker 1997, Rusinko 1997, Sobek et al 1998). On the other hand, numerous studies have shown that 'design' can provide an important integral resource.…”
Section: Introductionmentioning
confidence: 93%
“…generating ideas, concept development, post-launch etc.) (Lawrence and Lorsch, 1967;Souder, 1977;Gupta et al 1985;Carlsson, 1991;John and Hall, 1991;Griffin and Hauser, 1992;Griffin and Hauser, 1996;Kahn, 1996;Kahn andMentzer, 1998: Jassawalla andSashittal, 1998;Isaksson, 2005). The item, "IFI" concerns to the ability of a company to integrate different functional department in order to deliver higher customer value.…”
Section: Development Of Conceptual Modelmentioning
confidence: 99%
“…In particular, integration between the functions of PD and manufacturing has been recognized in research as an enabler of developing new products faster than competitors, reducing production costs and increasing product quality. However, Carlsson [14] concludes that although there is an agreement that integration and cooperation between the function of PD and manufacturing are crucial in product development, there are no satisfactory solutions owing to a number of barriers such as information (poor knowledge about the operations of other functions) and late manufacturing involvement. Moreover, Carlsson [13] shows that there are large differences between the functions of PD and manufacturing for various key variables.…”
Section: Related Workmentioning
confidence: 99%